2015
DOI: 10.1007/s11356-015-4189-0
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl substances in the Daling River with concentrated fluorine industries in China: seasonal variation, mass flow, and risk assessment

Abstract: In the present study, we investigated concentrations and composition profiles of perfluoroalkyl substances (PFASs) in surface water from the Daling River in different seasons. The highest concentration of ΣPFASs (9540 ng L −1 ) and dominant homologues were found in surface water collected in summer. Perfluorobutanoic acid (PFBA), perfluorobutane sulfonate (PFBS), and perfluorooctanoic acid (PFOA) were the dominant PFASs in four seasons with a total contribution of over 90 %. The discharge of two fluorine chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 51 publications
9
20
1
Order By: Relevance
“…Ohio River water PFOA concentrations in 2009 increased 1–3 ng/L at WWTP outfalls, compared to measurements immediately upstream (Emery et al, 2010). However, water PFOA concentrations are much lower (1.4–7.4 ng/L) in rivers solely contaminated by WWTPs (Huset et al, 2008; Muller et al, 2011a), while industrial PFAS discharges predominate over WWTPs in waters contaminated by both (Castiglioni et al, 2015; Valsecchi et al, 2015; Zhu et al, 2015). Because PFOA contamination in other waters is reported to persist hundreds of kilometers downstream of PFAS manufacturers (Valsecchi et al, 2015; Zhu et al, 2015), PFOA discharged into the Ohio River 209–666km upstream of our study area could have contaminated our participants’ drinking water.…”
Section: Discussionmentioning
confidence: 98%
“…Ohio River water PFOA concentrations in 2009 increased 1–3 ng/L at WWTP outfalls, compared to measurements immediately upstream (Emery et al, 2010). However, water PFOA concentrations are much lower (1.4–7.4 ng/L) in rivers solely contaminated by WWTPs (Huset et al, 2008; Muller et al, 2011a), while industrial PFAS discharges predominate over WWTPs in waters contaminated by both (Castiglioni et al, 2015; Valsecchi et al, 2015; Zhu et al, 2015). Because PFOA contamination in other waters is reported to persist hundreds of kilometers downstream of PFAS manufacturers (Valsecchi et al, 2015; Zhu et al, 2015), PFOA discharged into the Ohio River 209–666km upstream of our study area could have contaminated our participants’ drinking water.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, in recent years, PFASs have been frequently detected in different matrices including soil, water, sediment, biota, food stuff, human blood, etc. in China (Bao et al, 2010(Bao et al, , 2011Cai et al, 2012;Jin et al, 2003Jin et al, , 2009Liu et al, 2009;So et al, 2007;Wang et al, 2013a;Wu et al, 2012;Zhou et al, 2013;Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the PFAAs chemical compositions in each snow layers were similar but differed to those monitored for rain ( Figure S3). Previous study indicated that no temperature-related or wind direction-connected trend was observed for PFASs in rain from urban regions (Kwok et al, 2010), but the variation in PFAS compositional profiles found for different precipitation events has been shown to be strongly source-related (e.g., traffic conditions or industrial activity; Zhu et al, 2015). As the climate of Nam Co is influenced by westerly winds in winter and the Indian monsoon in summer, the differences in the compositional profiles of PFAAs may provide an indication of the emissions characteristics of different source regions.…”
Section: Possible Sources Of Pfaas In Precipitationmentioning
confidence: 96%